PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN ES KRIM WALL’S DI BALIKPAPAN - Irditya Mutiara Brilianti, Putri; Sukimin, Sukimin; Hermawansyah, Adi (Fakultas Ekonomi Universitas Balikpapan, 2025)
This research aims to analyze the partial and simultaneous influence of Product, Price, Place and Promotion variables on Wall's Ice Cream Purchase Decisions in Balikpapan. The type of research used is quantitative research. The number of samples in this study was 236 consumers who purchased Wall's ice cream in all stores in Balikpapan. The sampling technique used in this research is probability sampling. The data analysis used is descriptive analysis and multiple linear regression analysis. The test equipment used is instrument testing, classical assumption testing and hypothesis testing. The results of multiple linear regression analysis show that the Product, Price, Place and Promotion variables have a positive influence on the Purchasing Decision variable, either partially or simultaneously. Product variables have the most dominant influence on satisfaction with purchasing Wall's Ice Cream in Balikpapan